ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CARBON EMISSION DISCLOSURE DAN REAKSI SAHAM - Probosari, Desiana Catur; Kawedar, Warsito (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to investigate the effect of media exposure, industry types, company’s size, and environment performance on carbon emission disclosure and stock reaction. The sample is based on 33 manufacturing companies listed on The Indonesia Stock Exchange during period of 2013-2017. This reseach uses multiple regression analysis to test the research hypothesis. The result of this study show that industry types, company’s size, and evironment performance affect positive significantly on carbom emission disclosure. And industry types and carbon emission disclosure affect positive significantly on stock reaction.